Emotions, technology, and design - Tettegah, Sahron Y.; Noble, Safiya Umoja (Emotions and technology., 2016)
"Emotions, Technology, and Design addresses the emotional relationship between the objects and the subjects of design--objects being technologies, and subjects being technology users. Using philosophy and theory of emotional design as a foundation, the book discusses emotional design principles, the design and use of emoticons, and intelligent agents in a variety of settings. The volume thoroughly examines how technology design affects emotions and how to use that understanding in practical applications, and explores future research and directions."--Page 4 of cover.